2008
DOI: 10.1007/s11999-008-0143-5
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative Treatment of an Unstable Jefferson Fracture Using a Cervical Collar

Abstract: The treatment of unstable burst fractures of the atlas (Jefferson fractures) is controversial. Unstable Jefferson fractures have been managed successfully with either immobilization, typically halo traction or halo vest, or surgery. We report a patient with an unstable Jefferson fracture treated nonoperatively with a cervical collar, frequent clinical examinations, and flexion-extension radiographs. Twelve months after treatment, the patient achieved painless union of his fracture. The successful treatment con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Most recent biomechanical studies of atlas fractures have concluded that these fractures are usually caused by axial loading through the occiput 161718. Although there is agreement regarding treatment of stable Jefferson fractures, the optimal management of unstable Jefferson fractures remains controversial 619. The integrity of the transverse atlantal ligament (TAL) is the single most important factor in determining the method of treatment 20.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recent biomechanical studies of atlas fractures have concluded that these fractures are usually caused by axial loading through the occiput 161718. Although there is agreement regarding treatment of stable Jefferson fractures, the optimal management of unstable Jefferson fractures remains controversial 619. The integrity of the transverse atlantal ligament (TAL) is the single most important factor in determining the method of treatment 20.…”
Section: Discussionmentioning
confidence: 99%
“…There is a high prevalence of concomitant fractures of the axis, especially odontoid fractures 34. The unstable Jefferson fracture of C 1 is characterized by outward displacement of the lateral masses (LMD) in response to axial load 56. Treatment algorithms in determining surgical versus nonsurgical treatment of unstable Jefferson fractures have not reached a consensus, but treatment decisions are often based on the integrity of the transverse ligament and on the fact whether fractures occur in combination with other unstable spinal injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Until today, there are no definitive guidelines to treat atlas fractures, surgically or conservatively. Several authors argue that even unstable Jefferson fractures heal with a sufficient immobilization [ 10 12 ]. In contrast, critics report about high rates of nonunion and persisting pain following conservative treatment [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, critics report about high rates of nonunion and persisting pain following conservative treatment [ 13 , 14 ]. Atlas fractures appear unstable when the transverse atlantal ligament is ruptured [ 5 , 10 , 15 , 16 ]. If there is proven ligamentous insufficiency, many surgeons recommend operative stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 14 ] Fractures are best assessed by multidetector computed tomography (CT),[ 15 ] and although a lateral mass spread >6.9 mm shows disruption of the transverse ligament, magnetic resonance imaging (MRI) is a more sensitive indicator of ligament disruption or partial avulsion. [ 16 17 18 ] Long-term nonsurgical immobilization can cause irreversible arthrosis of the atlantoaxial joint,[ 19 ] and surgical fusion of C 1 to either C 2 or occiput restricts range of motion[ 20 ] causing degeneration of the subaxial cervical spine. [ 21 ] Recently, posterior motion-preserving ring osteosynthesis techniques that fix the fracture fragments in a reduced position so as to implement internal immobilization have been described.…”
Section: Introductionmentioning
confidence: 99%